An exploration of the quality of graduates of Philippine teacher education institutions - Olvido, Michelle Mae J.; Dayagbil, Filomena T.; Alda, Rivika C.; Uytico, Baby Jane; Rodriguez, Kim Francis R. (Frontiers in Education, 2024)
The study evaluated the quality of graduates of Philippine Teacher Education Institutions (TEIs) through the performance of the graduates in the Board Licensure Examination for Professional Teachers (BLEPT) and the teaching performance of the beginning teachers in their first three years of teaching. A nationwide survey study employing a descriptive cross-sectional design was conducted to 2,680 respondents from 16 regions in the country, selected using a multi-stage approach. Results revealed an increasing trend in the beginning teachers’ performance in the licensure examinations from 2017-2019. These teachers were also consistently averaging a rating of Very Satisfactory from 2019-2021 in their teaching performance. Furthermore, socio-economic status, grade point average in college, and grade level taught were other factors found to be significant in relation to teaching performance. As a result, a graduate's score on the teacher licensure exam has an impact on their success during their first three years of teaching. The dimensions of teacher quality in the country are anchored on the alignment of the outcomes and competencies in the written and tested curricula, effective program delivery, and qualified faculty which contribute to the high probability of passing the BLEPT that ultimately results in better teaching performance of beginning teachers. By focusing on these aspects, institutions can play a pivotal role in nurturing highly competent educators who make a lasting impact on the education system. The findings of this study serve as a valuable guide for educational policymakers and institutions striving to elevate the standard of teacher education across the country.